2019
DOI: 10.1097/brs.0000000000003033
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Costs and Opioid Use Associated With High-impact Chronic Spinal Pain in the United States

Abstract: Study Design. A descriptive analysis of secondary data. Objective. The aim of this study was to estimate health care costs and opioid use for those with high-impact chronic spinal (back and neck) pain. Summary of Background Data. The US National Pain Strategy introduced a focus on high-impact chronic pain—that is, chronic pain associated with work, social, and self-care restrictions. Chronic neck and low-bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 34 publications
1
34
0
Order By: Relevance
“…Spinal pain conditions, including low back pain and neck pain, are among the most common musculoskeletal pain conditions and contribute greatly to the high prevalence of chronic pain, with 6.0% of U.S. adults experiencing chronic spinal pain and 2.2% experiencing high-impact chronic spinal pain [3]. Spinal pain conditions carry high spine-related and overall healthcare costs, with an average of $3915 spent on spine-related healthcare and $9781 on overall healthcare costs per chronic spinal pain patient per year [3]. High-impact chronic spinal pain carries even greater direct costs ($5979 for spine-related healthcare and $14,661 for overall healthcare).…”
Section: Rationalementioning
confidence: 99%
“…Spinal pain conditions, including low back pain and neck pain, are among the most common musculoskeletal pain conditions and contribute greatly to the high prevalence of chronic pain, with 6.0% of U.S. adults experiencing chronic spinal pain and 2.2% experiencing high-impact chronic spinal pain [3]. Spinal pain conditions carry high spine-related and overall healthcare costs, with an average of $3915 spent on spine-related healthcare and $9781 on overall healthcare costs per chronic spinal pain patient per year [3]. High-impact chronic spinal pain carries even greater direct costs ($5979 for spine-related healthcare and $14,661 for overall healthcare).…”
Section: Rationalementioning
confidence: 99%
“…Neck pain (NP) and low back pain (LBP) are leading causes of disability and their burden is expected to increase due to the ageing population (James et al, 2018). Both NP and LBP have high direct and indirect social and economic costs (Herman, Broten, Lavelle, Sorbero, & Coulter, 2019; Vlaeyen et al, 2018) and are common causes of work absence, reduced work productivity and early disability pension (Hartvigsen et al, 2018; Hoy et al, 2014). The severe negative consequences, both for the society and affected individuals, underscore the importance of identifying modifiable factors that can be targeted to reduce the risk and improve prognosis of NP and LBP.…”
Section: Introductionmentioning
confidence: 99%
“…Opioid use and the use of other analgesics in combination with opioids increase with pain impact levels [9,43,44]. One study showed that early physical therapy for neck pain may decrease total treatment costs and the use of prescription medicines, including opioids [45].…”
Section: Discussionmentioning
confidence: 99%
“…Opioids only should be used after careful consideration and only for short-to medium-term treatment [8]. Previous studies have shown that excessive opioid use for neck pain is very common in the USA [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%